Analysis of Psychological Impact on Diabetes Patients in The Era of Pandemic Covid-19: A Literature Review - Maria Diana Durbin; Rizki Fitryasari; Makhfudli Makhfudli (Universitas Airlangga, 2021)
Introduction: Diabetics have several psychological problems associated with diabetes and its complications, which could be exacerbated during the Covid-19 pandemic. The purpose of this study is to analyze the types of psychological responses, efforts to prevent and overcome psychological impacts, and the results of efforts to deal with the psychological impacts experienced by diabetes in the Covid-19 pandemic era based on empirical studies in the last two years.Method: Journal search using a database Scopus, Science Direct. Proquest, and PubMed. The framework used to review is PICOS with inclusion criteria, namely English-language journals from 2019 to 2020. The study is divided into three major themes.Results: Of the ten studies that met the inclusion criteria, it was found that the types of psychological responses experienced by people with diabetes during the Covid-19 pandemic were stress, depression, and anxiety. Efforts to deal with psychological problems include telepsychiatry, telemedicine, telehealth, teleconsultation, self-care, and social support. The results obtained were in the form of low satisfaction levels, lifestyle changes, an increase in glycemic control, low anxiety levels, and high optimism with the Covid-19 situation, and a minimal impact on the psychological status of people with diabetes.Conclusion: It is important to pay attention to the psychological health of diabetics during the Covid-19 pandemic, and serious resources, planning, and action are needed to tackle this problem.